Book Review - Sow, Moussa (Journal of African Cinemas, 2010)
SAMBA FLIX NDIAYE: CINASTE DOCUMENTARISTE AFRICAIN, BY HENRI-FRANOIS IMBERT, PARIS, L'HARMATTAN, 2007 359 pp., 31 (paperback), ISBN: 978-2-296-03862-2
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qYWMuMi4yLjE5NV81